IMPROVEMENT OF INVENTORY ACCOUNTING IN BUDGET ORGANIZATIONS - Xolmurodova Durdona Otamurod qizi; Ostonokulov Azamat Abdukarimovich (TADQIQOTLAR, 2025)
Abstract. Inventory accounting is a critical aspect of financial management in budget  organizations.  Accurate  inventory  management  ensures  optimal  resource allocation  and  financial  stability.  However,  many  budget  organizations  struggle  to maintain  effective  inventory  accounting  practices  due  to  a  lack  of  standardized procedures,  technological  limitations,  and  human  errors.  This  article  examines  the challenges  faced  by  budget  organizations  in  inventory  accounting  and  proposes strategies  for  improvement.  These  include  implementing  standardized  procedures, adopting  technology,  improving  employee  training,  and  fostering  a  culture  of continuous improvement. By adopting these recommendations, budget organizations can enhance their inventory accounting practices, leading to increased efficiency and financial stability.